PUBLIC ART: Structural Restraints and How to Deal with Them - Schawelka, Karl (Farol, 2015)
In order to understand the present situation, some historical considerations might be useful. I will start with an episode told by Vasari. According to him, in 1504 the young and relatively little-known Michelangelo was given a huge block of marble to work on, which was however deemed untreatable because of a crack on its bottom. As we all know, he nevertheless made a tremendous success of the commission, creating the famous David. This sculpture was originally meant to adorn the outside of the clerestory wall of the cathedral as part of a programme consisting of several heroes from the Old Testament. But when Michelangelo had finished his work, everyone agreed, that it deserved a better location. [...]